Expected and achieved outcomes of child-related tax benefits in Germany - Hybka, Małgorzta Magdalena (Oczekiwane i faktyczne rezultaty stosowania podatkowych instrumentów polityki prorodzinnej w Niemczech, 2020)
Germany is among the countries applying multiple and diversified instruments to foster the economic well-being of families with children. The first instruments of this kind were implemented as early as in the 1930s. Since then the governments have been pursuing the family policy goals in a systematic and continuous way. Germany is also among countries affected by a relatively low female fertility rate and deaths exceeding births for nearly half a century. Before the refugee crisis the country was also experiencing a negative population growth rate. This paper reviews selected family policy means currently in force in Germany. It concentrates on family-friendly tax measures, and is aimed at evaluating the current demographic situation of Germany and the costs of family policy instruments, bearing in mind the diversity and long history of their application. Moreover it compares the expected and actually accomplished effects of the application of the family-friendly tax measures
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 52-63
Keywords: tax preferences; family policy measures; Germany; zasiłki prorodzinne; podatkowe instrumenty polityki prorodzinnej; Niemcy